Positron Emission Tomographic Imaging of CXCR4 in Cancer: Challenges and Promises - Guillaume Pierre Charles George; Federica Pisaneschi; Quang-Dé Nguyen; Eric Ofori Aboagye (Molecular Imaging)
Molecular imaging is an attractive platform for noninvasive detection and assessment of cancer. In recent years, the targeted imaging of the C–X–C chemokine receptor 4 (CXCR4), a chemokine receptor that has been associated with tumor metastasis, has become an area of intensive research. This review article focuses on positron emission tomography (PET) and aims to provide useful and critical insights into the application of PET to characterize CXCR4 expression, including the chemical, radiosynthetic, and biological requirements for PET radiotracers. This discussion is informed by a summary of the different approaches taken so far and a comparison of their clinical translation. Finally, our expert opinions as to potential future advances in the field are expressed.